Digital Marketing Strategies in the Public Sector of Tourism: Enhancing Promotion and Engagement in the Tourism Industry - Ahmad Wahidiyat Haedar (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to investigate the effectiveness of digital marketing strategies in the public sector of tourism and their role in enhancing promotion and engagement within the tourism industry. The background of the study highlights the increasing importance of digital platforms in marketing and the need for the public sector to adopt effective strategies to promote tourism. The objective of this research is to analyze the methods employed by public sector organizations in implementing digital marketing strategies and to assess their impact on promotion and engagement in the tourism industry. To achieve this objective, a mixed-methods approach was utilized, combining quantitative analysis of digital marketing campaigns and qualitative interviews with key stakeholders in the public sector of tourism. The quantitative analysis involved evaluating the reach and engagement metrics of various digital marketing initiatives, including social media campaigns, email marketing, and website optimization. The qualitative interviews provided insights into the decision-making processes, challenges, and success factors associated with implementing digital marketing strategies. The findings of this research reveal that effective digital marketing strategies play a crucial role in promoting tourism and enhancing engagement in the public sector. The analysis of digital marketing campaigns demonstrates the significant impact of social media platforms, targeted email marketing, and website optimization in reaching and engaging with the target audience. Additionally, the interviews highlight the importance of collaboration between public sector organizations, private sector stakeholders, and local communities in designing and implementing effective digital marketing strategies.